Analysis of PI-RADS 4 cases: Management recommendations for negatively biopsied patients. Issue 113 (April 2019) - Ullrich, T.; Arsov, C.; Quentin, M.; Laqua, N.; Klingebiel, M.; Martin, O.; Hiester, A.; Blondin, D.; Rabenalt, R.; Albers, P.; Antoch, G.; Schimmöller, L.
Highlights: Re-biopsy of obvious, peripheral, negatively biopsied PI-RADS-4-lesions is recommended. Negatively biopsied transition zone confined PI-RADS-4-lesions with overlaying signs of severe stromal hyperplasia rarely contain csPCa. Targeted MR/US fusion biopsy alone can miss some csPCa. In uncertain cases PSAD should be considered for biopsy decision. Abstract: Purpose: To evaluate if subgroups of patients assigned to MRI category PI-RADS 4 regarding clinical and MRI imaging aspects have distinct risks of prostate cancer (PCa) to facilitate adequate clinical management of this population, especially after negative targeted biopsy. Methods: This prospective, IRB approved single center cross-sectional study includes 931 consecutive patients after mp-MRI at 3 T for PCa detection. 193 patients with PI-RADS assessment category 4 received subsequent combined targeted MRI/US fusion-guided and systematic 12-core TRUS-guided biopsy as reference standard and were finally analyzed. The primary endpoint was PCa detection of PI-RADS 4 with MRI subgroup analyses. Secondary endpoints were analyses of clinical data, location of PCa, and detection of targeted biopsy cores. Results: PCa was detected in 119 of 193 patients (62%) including clinically significant PCa (csPCa; Gleason score ≥3 + 4 = 7) in 92 patients (48%). MRI subgroup analysis revealed 95% PCa (73% csPCa) in unambiguous PI-RADS 4 index lesions without additional, interfering signs of prostatitis in the peripheral zone or overlaying signs of severe stromal hyperplasia in the transition zone according to PI-RADS v2. Transition zone confined PI-RADS-4-lesions with overlaying signs of stromal hyperplasia showed PCa only in 11% (4% csPCa). Targeted biopsy cores missed the csPCa index lesion in 7% of the patients. PSA density (PSAD) was significantly higher in PCa patients. Conclusions: Small csPCa can reliably be detected with mp-MRI by experienced readers, but can be missed by targeted MR/US fusion biopsy alone. Targeted re-biopsy of unambiguous (peripheral) PI-RADS-4-lesions is recommended; whereas transition zone confined PI-RADS-4-lesions with overlaying signs of stromal hyperplasia might be followed-up by re-MRI primarily.